Analysis of antithyroid drug residues in food animals. (August 2012) - Boison, Joe
In the late 1970s, concerns were raised regarding why antithyroid drugs were being administered to food animals to promote growth despite the fact that they had been implicated as being carcinogenic and teratogenic; the growth promotion process produced an inferior quality meat with increased water retention in the animal's gastrointestinal tract. An increased incidence of aplasia cutis (a characteristic scalp defect) in consumers in Spain was linked to an increased consumption of antithyroid-contaminated meat. Therefore, to protect human health, the EU banned the use of antithyroid drugs in food animal production in 1981. This article reviews the impact of this regulatory decision on the regulatory analysis of these compounds in foods of animal origin. It discusses the physiology of the thyroid gland, the chemistry of antithyroid drugs and critically evaluates the suitability of the analytical methods that have been developed and validated to support enforcement of the regulation.